The stress regulator FgWhi2 and phosphatase FgPsr1 play crucial roles in the regulation of secondary metabolite biosynthesis and the response to fungicides in Fusarium graminearum - Jie Zhang; Han Gao; Fuhao Ren; Zehua Zhou; Huan Wu; Huahua Zhao; Lu Zhang; Mingguo Zhou; Yabing Duan (Journal of Integrative Agriculture)
In yeast, the stress-responsive protein Whi2 interacts with phosphatase Psr1 to form a complex that regulates cell growth, reproduction, infection, and the stress response. However, the roles of Whi2 and Psr1 in Fusarium graminearum remain unclear. In this study, we identified homologous genes of WHI2 and PSR1 in F. graminearum and evaluated their functions by constructing deletion mutants. By comparing the responses of the mutants to different stressors, we found that FgWHI2 and FgPSR1 were involved in responding to osmotic, cell wall and cell membrane stresses, while also affecting the sexual and asexual reproduction in F. graminearum. Our studies demonstrated that FgWHI2 and FgPSR1 regulate the biosynthesis of ergosterol and the transcriptional level of FgCYP51C, which is a CYP51 paralogues unique to Fusarium species. This study also found that the deoxynivalenol (DON) production of FgWHI2 and FgPSR1 deletion mutants was reduced by ≥90% and DON production was positively correlated with the transcriptional levels of FgWHI2 and FgPSR1. In addition, we observed that FgWHI2 and FgPSR1 were involved in regulating the sensitivity of F. graminearum to chlorothalonil, fluazinam, azoxystrobin, phenamacril, and oligomycin. This study revealed cross-resistance between chlorothalonil and fluazinam. Meanwhile, chlorothalonil and fluazinam inhibited DON biosynthesis by altering the normal expression of FgWhi2 and FgPsr1. Interestingly, the subcellular localization of FgWhi2 and FgPsr1 was significantly altered after treatment with chlorothalonil and fluazinam, with increased co-localization. Collectively, these findings indicate that FgWHI2 and FgPSR1 play crucial roles in stress response mechanisms, reproductive processes, secondary metabolite synthesis, and fungicide sensitivity in F. graminearum.